Cardiac involvement in critically ill patients with leptospirosis: A prospective study using myocardial deformation imaging. Issue 8 (December 2020) - Mathew, Anoop; Shanks, Miriam; Punnoose, Eapen; Fischer, Louie; Koshy, George; Potluri, Rahul; Bainey, Kevin R
Background: Myocardial inflammation often complicates leptospirosis, a re-emerging global zoonosis. Leptospirosis associated myocardial dysfunction is equivocal and the pattern of cardiac involvement may not differ from that of sepsis associated myocarditis. Methods: We prospectively compared cardiac involvement in 113 intensive care unit patients with severe leptospirosis to 31 patients with sepsis syndrome using a comprehensive assessment comprising of clinical presentation, electrocardiography, two-dimensional echocardiography (with global longitudinal strain calculation), and cardiac biomarker evaluation. Binomial logistic regression was performed to identify independent predictors of left ventricular systolic dysfunction in leptospirosis. Results: Compared to sepsis syndrome, leptospirosis patients were younger, had higher body mass index measurements and were more likely to be smokers. Electrocardiography abnormalities were common and similar in both groups. Myocardial systolic dysfunction was common in both groups (leptospirosis: 55.86% vs sepsis syndrome: 51.61%, p =0.675) with subclinical left ventricular systolic dysfunction (characterized by abnormal global longitudinal strain and normal left ventricular ejection fraction) being most frequent followed by isolated right ventricular systolic dysfunction, isolated left ventricular systolic dysfunction, and bi-ventricular systolic dysfunction (leptospirosis: 31.43%, 18.42%, 13.16%, 10.53%, respectively; sepsis syndrome: 22.22%, 12.00%, 12.00%, 8.00%, respectively ( p >0.05 for each comparator)). Leptospirosis patients had a trend towards greater troponin-T elevation (61.0% vs 40.0%, p =0.057). ST-segment elevation and elevated troponin were independent predictors of reduced left ventricular ejection fraction in leptospirosis. Conclusions: Cardiac involvement in leptospirosis appears to be similar to that of sepsis syndrome, with myocardial systolic dysfunction being common. As such, clinical vigilance pertaining to cardiac status is paramount in these high-risk patients.